Bedaquiline and multidrug-resistant tuberculosis: a systematic and critical analysis of the evidence. Issue 2 (February 2016) - Pontali, Emanuele; Sotgiu, Giovanni; D'Ambrosio, Lia; Centis, Rosella; Migliori, Giovanni Battista
The importance of adequately managing multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) cases for TB control and elimination are underlined in the new World Health Organization (WHO) "End TB Strategy" [1, 2] as part of pillar one (integrated, patient-centred care and prevention; element 2: treatment of all people with TB including drug-resistant TB, and patient support) and in the recently published "Framework towards TB elimination in low incidence countries" in its priority action 5 (optimise the prevention and care of drug-resistant TB) and the related background documents [3–5]. Furthermore, both in the End TB Strategy (pillar 3: intensified research and innovation) and in the Framework towards TB elimination in low incidence countries (priority action 7: invest in research and new tools) the need for new anti-TB drugs is strongly emphasised [1, 3, 6]. The reasons why new anti-TB drugs are needed are rather obvious if you look closely at the dimensions of the MDR-TB epidemic and the treatment successes achieved so far. Systematic review of the available scientific evidence on the role of bedaquiline in new effective M/XDR-TB regimens http://ow.ly/V68ZF